Du corps en état de langage - Maria de Jesus Cabral (Carnets)
Most relevant in Lesson, Roland Barthes’s reflexions on language rely on a conception of literature allowing for fruitful interactions with other human and social sciences which focus on the question of man and language today. This is the case of Narrative Medicine, linking literature and medicine practices in a time when the instrumental evolution of medicine calls for new approaches able to take into account the relational dimension and subjectivity.